Mapping of key performance indicators for palliative care in intensive care settings: A scoping review protocol - King, Yvonne (HRB Open Science, 2026)
Background: Palliative care integration in intensive care units (ICUs) is becoming increasingly important in terms of patient-centred care delivery. While both generalist (primary) palliative care provided at the ICU level and specialist palliative care (SPC) services support delivery, there is limited clarity regarding how such integration and care can be measured. Key performance indicators are generally identified as indicators of the quality of healthcare. However, relevant palliative care key performance indicators for the ICU are poorly defined and vary across policies, regulations, and the literature. Aim: To identify and map key performance indicators to inform a domain-based framework for evaluating palliative care delivery in ICUs. Methods: This study will be conducted as a scoping review following the PRISMA-ScR guidelines. We will undertake a systematic search of peer-reviewed records, grey literature, national health system sources, regulatory bodies, and professional organisations. Once extracted, we will analyse the key performance indicators and group them into domains reflecting both generalist and specialist palliative care delivery. Conclusions: This will result in a comprehensive synthesis of key performance indicators and a developed structured framework to support the evaluation and implementation of palliative care delivery in the ICU.
PUBLISHED (open peer review in progress)
Keywords: Critical Care; End-of-Life Care; Intensive Care Units; Key Performance Indicators; Palliative Care; Quality Indicators; Scoping Reviews; Ageing; Cancer; International Integration; Acute Care Nursing; Acute care management, early detection deterioration; Clinical : Critical Care Nursing; Clinical : Critical Care Nursing / Decision Making; Critical Care; DECISION MAKING; INTENSIVE CARE; Nurse communication in intensive care; Nursing; PALLIATIVE CARE; Palliative and end of life care; Palliative care nursing; key performance indicators; quality indicators; Health; Policy